Introductory Remarks on the Issue "The Crisis of Representation" - Deibl, Jakob Helmut (Interdisciplinary journal for religion and transformation in contemporary society, 2018)
The introductory remarks of the issue J-RaT 7 function as an invitation to deal with the topic of the Crisis of Representation. The Crisis, in this context, has not only a political and economic dimension, but a cultural, aesthetic and religious one as well. Thus, a serious inquiry into this complex and multidimensional phenomenon requires an interdisciplinary approach. The issue targets the phenomena at hand through 15 contributions. One common aim that holds the issue together is the analysis of the nature of the crisis, which helps to find suitable theoretical frameworks. On the other hand, the term itself functions as a tool that enables the analysis of specific societal developments.